Percepção do mercado contratante sobre os pós-graduados com título de MBA - Queiroz, Marcellus Salazar de (2008)
Each day increases the requirements for labor-management specialist. As a result of this increased demand, the market also will require more about this workforce that is the input to business results. This requires the educational institutions to be very aligned with the market, aiming to offer the fullness that meets the new requirements of these organizations. This research aimed to raise the perception of recruiters, noting what factors they consider relevant at the time of recruitment of candidates post-graduates with an MBA. The aim was to take into account how certain characteristics associated with the training of professional impute greater weight, or not, in the selection process, always assuming the premise that the MBA is an important component in the decision making process for the recruitments under discussion. The work was carried out using a qualitative research, from in-depth interviews conducted with contractors from medium and large enterprises in the cities of Rio de Janeiro and São Paulo. The results observed allowed create categories such as technical knowledge, professional experience, differential factor, skill and decision-making, flexibility, leadership, team working, communication and interpersonal relationships, capacity for learning and personal development. On the aspect of the institution, the brand of MBA also showed any importance. The study also highlights the negative perception, generated by excessive competition, despite the preservation of the parameters of quality, generating a loss of prestige of the institution from the view of recruiters. Finally the work casts insights on the subject, and can be useful as a basis for new research and developments.